INNV-27. SAFETY OF DIRECT ORAL ANTICOAGULANTS AS COMPARED TO LOW MOLECULAR WEIGHT HEPARIN IN TREATING VENOUS THROMBOEMBOLISM IN PATIENTS WITH PRIMARY BRAIN TUMORS AND BRAIN METASTASES. (14th November 2022) - Ali, Assad; Shah, Nirja; Santiago, Raphael Bastianon; Mandel, Mauricio; Obrzut, Michal; Borghei-Razavi, Hamid; Adada, Badih; Ranjan, Surabhi
Abstract: INTRODUCTION: Patients with brain tumors (PBTs) have a 20 to 30% incidence of venous thromboembolism (VTE) Recently, new direct oral anticoagulants (DOACs) such as rivaroxaban, apixaban, dabigatran and edoxaban, have gained popularity in treating VTE in cancer patients due to ease of administration and favorable safety profile. DOACs are also being used in treating VTE in in PBTs. While clinical trials have established the safety of DOAC use in systemic cancers, there is only limited literature on safety of DOAC in PBTs. In this review, we explore all prospective and retrospective studies to evaluate the safety of DOAC in comparison to LMWH in treating VTEs in PBTs. METHODS: A search on PubMed database using keywords "Direct Oral Anticoagulant, " OR "Oral Anticoagulant, " AND "Cancer, " AND "Clinical Trial" was performed for clinical trials. Another search using keywords "Direct Oral Anticoagulants, " OR "Oral Anticoagulant, " AND "Brain Tumor, " AND "Retrospective." was performed for retrospective studies. RESULTS: Of 359 clinical trials in cancer patients, only 4 evaluating DOAC versus LMWH, included PBTs– Hokusai, Select D, ADAM VTE and EINSTEIN-DVT/PE. Four retrospective studies (Lee 2021, Carney 2019, Schwartz 2021 and Leader 2021) were identified.These four clinical trials enrolled a very limited number of PBTs (0.7, 1.5%, 2.7% and 6.8% of all patients). The risk of ICH with DOAC as compared to LMWH was low in Hokusai trial (OR = 0.93; CI=0.14-5.9) and uninformative in other 3 trials (0 episodes of ICH in either/both groups). All four retrospective studies showed no increase in incidence of ICH in the DOAC versus LMWH group in PBTs. CONCLUSION: In the small number of prospective and retrospective studies which have evaluated the safety of DOAC in comparison to LMWH in brain tumors, the use of DOAC appears to be safe with no increase in the risk of ICH over LMWH.